Transcriptomic analysis of pulmonary artery smooth muscle cells identifies new potential therapeutic targets for idiopathic pulmonary arterial hypertension. (15th May 2020) - Gorr, Matthew W.; Sriram, Krishna; Muthusamy, Abinaya; Insel, Paul A.
Abstract : Background and Purpose: Pulmonary arterial hypertension (PAH, type 1 pulmonary hypertension) has a 3‐year survival of ~50% and is in need of new, effective therapies. In PAH, remodelling of the pulmonary artery (PA) increases pulmonary vascular resistance and can result in right heart dysfunction and failure. Genetic mutations can cause PAH but it can also be idiopathic (IPAH). Enhanced contractility and proliferation of PA smooth muscle cells (PASMCs) are key contributors to the pathophysiology of PAH, but the underlying mechanisms are not well understood. Experimental Approach: We utilized RNA‐sequencing (RNA‐seq) of IPAH and control patient‐derived PASMCs as an unbiased approach to define differentially expressed (DE) genes that may identify new biology and potential therapeutic targets. Key Results: Analysis of DE genes for shared gene pathways revealed increases in genes involved in cell proliferation and mitosis and decreases in a variety of gene sets, including response to cytokine signalling. ADGRG6/GPR126, an adhesion G protein‐coupled receptor (GPCR), was increased in IPAH‐PASMCs compared to control‐PASMCs. Increased expression of this GPCR in control‐PASMCs decreased their proliferation; siRNA knockdown of ADGRG6/GPR126 in IPAH‐PASMCs tended to increase proliferation. Conclusion and Implications: These data provide insights regarding the expression of current and experimental PAH drug targets, GPCRs and GPCR‐related genes as potentially new therapeutic targets in PAH‐PASMCs. Overall, the findings identify genes and pathways that may contribute to IPAH‐PASMC function and suggest that ADGRG6/GPR126 is a novel therapeutic target for IPAH.